The Concept of the Border in the Polish Consciousness and its Impact on the Culture and Identity of the Central and Eastern Europe in the Modern Period - Janusz, Smołucha (Études sur la Région Méditerranéenne, 2023)
The aim of the article is to discuss the notion of the border in Polish consciousness as it was developed in the early modern period. The concept can be interpreted at three levels: spiritual, moral and political and can be seen in the light of linguistic, cultural, political and economic exchange between Poland and neighbouring countries. It can be argued that its very nature had both Christian and classical foundations and to a large extend was shaped by the policy and modus operandi of the Jesuit Order. The terms such as “intemarium”, “bulwark of Christianity” and “borderlands” were also strongly associated with the chivalric culture, in which not only a particular territory but also spiritual values and moral virtues were defended and promoted. These high ideas could not be put into action, and much less fulfilled, without the grounding paradigm which found its finest expression in the concept of miles Christianus – a personal role model patterned after Christ and the Church Triumphant, which combined the idea of spiritual struggle for the salvation of one’s soul with a physical combat waged in defence of Latin civilization against schismatics and Muslims.